2022
DOI: 10.2147/ppa.s373393
|View full text |Cite
|
Sign up to set email alerts
|

A Smart-Phone App for Fluid Balance Monitoring in Patients with Heart Failure: A Usability Study

Abstract: Background For a long time, fluid balance monitoring has been one of the most difficult problems in the management of patients with heart failure (HF). There is considerable interest in technology-facilitated fluid balance monitoring. However, little is known about patient acceptance and the use of mobile technology for fluid balance monitoring. Objective The aim of this study was to develop a mobile app for technology-facilitated fluid balance monitoring and to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…The Mobile System for Elderly Monitoring (SMAI) that monitors elderly patients with functional loss and assists caregivers, scored slightly lower on the SUS scale, i.e., 77.42, SD =9.14 [24], indicating a "good" to "excellent" level of usability. The I-Self-Care mobile app that monitors fluid balance in patients with heart failure obtained the mean SUS score of 81.74 (SD 5.44) among 36 patients and 80.80 (SD 13.26) among 28 nurses [25]. Unfortunately, as noted by the authors of the systematic review by Lee et al [22], many mobile apps designed as educational tools for the health professions lack usability assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mobile System for Elderly Monitoring (SMAI) that monitors elderly patients with functional loss and assists caregivers, scored slightly lower on the SUS scale, i.e., 77.42, SD =9.14 [24], indicating a "good" to "excellent" level of usability. The I-Self-Care mobile app that monitors fluid balance in patients with heart failure obtained the mean SUS score of 81.74 (SD 5.44) among 36 patients and 80.80 (SD 13.26) among 28 nurses [25]. Unfortunately, as noted by the authors of the systematic review by Lee et al [22], many mobile apps designed as educational tools for the health professions lack usability assessments.…”
Section: Discussionmentioning
confidence: 99%
“…W przypadku Mobile System for Elderly Monitoring (SMAI) do monitorowania starszych pacjentów z dysfunkcją mobilności i wsparcia opiekunów w opiece, uzyskano nieco niższe oceny w skali SUS 77,42, SD =9,14 [24], co klasyfikuje w przedziale od "dobrego" do "doskonałego" poziomu użyteczności. W ocenie użyteczności skalą SUS aplikacji mobilnej I-Self-Care do monitorowania równowagi płynów u pacjentów z niewydolnością serca, średnie wyniki SUS wyniosły 81,74 (SD 5,44) wśród 36 pacjentów i 80,80 (SD 13,26) wśród 28 pielęgniarek [25]. Niestety wiele aplikacji mobilnych przygotowywanych, jako pomoc edukacyjna, w zawodach medycznych nie Nursing students' experiences with the "DiagNurse" mobile app to support clinical patient assessment -a pilot study posiada ocen jej użytecznosci, co podkreślają autorzy przeglądu systematycznego technologie mobilne w edukacji pielęgniarskiej [22].…”
Section: Dyskusjaunclassified
“…Although 23 of the existing tools were explicitly intended for HCPs [14,43,46,47,[76][77][78][79][80][81][82][83][84][85][86][93][94][95][96][97][98][99][100], none of these were complete; rather, they were too focused on specific conditions, or their theoretical justifications or development processes were not described. Such omissions make it difficult for HCPs in clinical practice to comprehensively but feasibly describe and evaluate eHealth apps in a standardized way to guide the recommendation of relevant, reliable, and high-quality apps to their patients [11,13,14].…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…There are 4 studies Randomized Controlled Trial, 1 Pilot Randomized Controlled Trial, 1 Protocol Randomized Controlled Trial, 1 cross-sectional study, 2 systematic review,3 articles reviews,1 usability studies, 1 Pilot clinical studies and 1 descriptive qualitative. All studies (Creber et al, 2016;Davoudi et al, 2020;Dorsch et al, 2021;Giordan, Tong, et al, 2022;Indraratna et al, 2020;Jain et al, 2019;Johnson et al, 2022;Leigh et al, 2022;Park & Lee, 2021;Schmaderer et al, 2021;Seto et al, 2012;Shen et al, 2022), which included reported uploading of data on self-monitoring of self-care management such as monitoring symptoms, weight, physical activity, medication adherence, and blood pressure in heart failure patients. Only one study implemented a monitoring application intakeoutput fluids, symptoms, hospitalization information and notes on diuretic use real time namely (Shen et al, 2022).…”
Section: Characteristic Articlesmentioning
confidence: 99%
“…All studies (Creber et al, 2016;Davoudi et al, 2020;Dorsch et al, 2021;Giordan, Tong, et al, 2022;Indraratna et al, 2020;Jain et al, 2019;Johnson et al, 2022;Leigh et al, 2022;Park & Lee, 2021;Schmaderer et al, 2021;Seto et al, 2012;Shen et al, 2022), which included reported uploading of data on self-monitoring of self-care management such as monitoring symptoms, weight, physical activity, medication adherence, and blood pressure in heart failure patients. Only one study implemented a monitoring application intakeoutput fluids, symptoms, hospitalization information and notes on diuretic use real time namely (Shen et al, 2022). All studies involve the use of an app smartphone.…”
Section: Characteristic Articlesmentioning
confidence: 99%